Designing PALUGADA (Practice and Learn Using Grammar Learning Media) for Beginner Students - Ulfa Wulan Agustina (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2021)
ABSTRACT Palugada is practice and learn using grammar learning media. This study aims to design a Grammar Learning Media that is focused on beginner students in learning English at school. The research method used is the Research and Development (R&D) method using the ADDIE model, this model consists of five parts, namely analysis, design, development, implementation, and evaluation. There are two media feasibility validations for this product. The first is material validation, and the second is media validation. Both have been validated by their respective expert validators before being tested on students. Data collection was done by using a questionnaire. The results of the implementation are in the form of an assessment of student work and media suggestions. The results of the implementation show that the average acquisition percentage of the assessment is 97.77% in the 'very good' category. So, based on the results of this study, it can be concluded that the application of grammar learning media is suitable for helping eighth grade student. KEYWORDS: Palugada, Learning media, Beginner Students ABSTRAK Palugada adalah latihan dan pembelajaran menggunakan media pembelajaran grammar. Penelitian ini bertujuan untuk merancang Media Pembelajaran Grammar yang difokuskan pada siswa pemula dalam pembelajaran bahasa Inggris di sekolah. Metode penelitian yang digunakan adalah metode Research and Development (R&D) dengan menggunakan model ADDIE, model ini terdiri dari lima bagian yaitu analisis, perancangan, pengembangan, implementasi, dan evaluasi. Ada dua validasi kelayakan media untuk produk ini. Yang pertama adalah validasi materi, dan yang kedua adalah validasi media. Keduanya telah divalidasi oleh validator ahli masing-masing sebelum diujikan pada siswa. Pengumpulan data dilakukan dengan menggunakan kuesioner. Hasil implementasi berupa penilaian karya siswa dan saran media. Hasil implementasi menunjukkan bahwa rata-rata perolehan persentase penilaian adalah 97,77% dengan kategori sangat baik. Jadi, berdasarkan hasil penelitian ini dapat disimpulkan bahwa penerapan media pembelajaran grammar cocok untuk membantu siswa kelas VIII. KATAKUNCI: Palugada, Learning media, Beginner students